1972
DOI: 10.1021/jf60180a073
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal and the anticholinesterase activity of m-acylamidophenyl and m-thioureidophenyl N-methylcarbamates

Abstract: SACHER, OLINand only one sample of 2,4-D contained measurable amounts of the hexa isomers. The hexa isomers present presumably were there because of tetrachlorophenol impurities which condensed with each other. Higher dioxins were found in some samples of several other pesticides, including erbon, tetradifon, ronnel, sesone, and DMPA.The dioxin content of the 20 chlorophenol samples is also presented in Table 111. No TCDD was detected in any sample at levels above 0.5 ppm. However, the higher dioxins were plen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1973
1973
2008
2008

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Cholinesterase Determinations. The procedure described by Sacher and Olin (1972) was used for the enzyme determinations. Briefly, the cholinesterase was incubated with the carbamates for 12 min, utilizing a Technicon Autoanalyzer apparatus (Winter, 1960).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholinesterase Determinations. The procedure described by Sacher and Olin (1972) was used for the enzyme determinations. Briefly, the cholinesterase was incubated with the carbamates for 12 min, utilizing a Technicon Autoanalyzer apparatus (Winter, 1960).…”
Section: Methodsmentioning
confidence: 99%
“…Two-day-old susceptible female houseflies (Musca domestica L. Snaidm strain) were utilized for the fly toxicity measurements. Flies were treated topically as described by Sacher and Olin (1972). For the synergism studies flies were treated as above with a carbamate-2,3methylenedioxynaphthalene combination at a 1:1 ratio (w/w).…”
Section: Methodsmentioning
confidence: 99%
“…Replacing the carbamate linkage (OC (O) N) with thiol (SC=O), thiono (OC=S), or dithio (SC=S) reduced the antiChE activity of 2-isopropylphenyl N,N-dimethylcarbamate by 12 to 40 times (Petrovskii 1970). Fifty-nine new N-methyl and N N N,N-dimethylcarbamates, meta-N N acylamidophenyl and meta-thioureidophenyl, were synthesized and tested as inhibitors of fl y and bovine ChEs (Sacher and Olin 1972). Structurefl activity correlation indicated that maximal antiChE activity was associated with a definite size of the alkyl substituent on the amide or thiourea groupfi ing, with four to six carbons producing the most potent inhibitors.…”
Section: Halogen-substituted Phenyl- Thio- and Nitrophenylcarbamatesmentioning
confidence: 99%
“…Serum tests that measure thyroid activity include the following (compiled from Kasten et al, 2001;Kuritzky, 2001;Noble, 2001;Sacher, McPherson, & Campos, 2000;Shames & Shames, 2001).…”
Section: Measuring Thyroid Activitymentioning
confidence: 99%